Clinical and morphological study of calf enlargement following S-1 radiculopathy - Osvaldo J. M. Nascimento; Marcos R. G. de Freitas; Myrian D. Hahn; Abelardo Q. C. Araújo (Arquivos de Neuro-Psiquiatria)
Calf enlargement following sciatica is a rare condition. It is reported the case of a 28-year-old woman who complained of repeated episodes of lower back pain radiating into the left buttock and foot. One year after the beginning of her symptoms, she noticed enlargement of her left calf. X-ray studies disclosed L5-S1 disk degeneration. EMG showed muscle denervation with normal motor conduction velocity. Open biopsies of the gastrocnemius muscles were performed. The left gastrocnemius muscle showed hypertrophic type 2 fibers in comparison with the right gastrocnemius. Electron microscopy showed mildly increased number of mitochondria in these fibers. A satisfactory explanation for denervation hypertrophy has yet to be provided.